Handbook for health care ethics committees - Post, Linda Farber (John Hopkins University Press, 2015)
Handbook for Health Care Ethics Committees was the first book of its kind to address the myriad responsibilities faced by ethics committees, including education, case consultation, and policy development. Adopting an accessible tone and using a case study format, the authors explore serious issues involving informed consent and refusal, decision making and decisional capacity, truth telling, the end of life, palliative care, justice in and access to health care services, and organizational ethics.